The measurement of the influence of the adhesion loss on the dynamic load of the drive reaction rod on the roller rig - Vojtěch Dybala (Acta Polytechnica CTU Proceedings, 2023)
The dynamic behaviour and dynamic phenomena in traction drives of railway vehicle has been studied for decades. Generally, in these days the motivation for this research is to look for answers related with service problems, which has been risen, e.g. an overloading of mechanical components as wheelsets or an intention to improve control systems of traction drives of railway vehicles. This problematic has also motivated the research at the Faculty of Mechanical Engineering at the Czech Technical University (CTU) in Prague. Nowadays it is also usual, that the main research tool has been a simulation based on a mathematical model of a railway vehicle or its specific components, as testing on real vehicles is very demanding regarding costs. However, there is an alternative – a roller rig. At the CTU in Prague there has been modernized the second roller rig for purposes of measurement regarding the torsion dynamics research, to support PhD students for their theses and possibly to extend the education for students oriented on the railway vehicle’s design. This contribution brings results of measurements just from the problematics of torsion oscillations and dynamics. Specifically, further presented measurements are on the loss of the adhesion in the contact of the wheelset and rollers, as the substitution for the railway, its impact on the reaction rod overloading and study of the axle load influence on the transition phenomena.